IMPLEMENTASI PENGELOLAAN DANA ZAKAT, INFAK, SEDEKAH (ZIS) PADA RUMAH SINGGAH PASIEN (RSP) LEMBAGA AMIL ZAKAT (LAZ) INISIATIF ZAKAT INDONESIA (IZI) - Ahmad Fahmi Abdurrahman; Sri Herianingrum (Universitas Airlangga, 2019)
This study purpose to recognize the implementation of ZIS (Zakat, Infak, Shadaqah) fund management at LAZ Indonesia Zakat Initiative (IZI) East Java in managing the Patient Shelter House program. The author of this study uses descriptive qualitative methods using a case study approach. The object of this study is LAZNAS Indonesian zakat initiative, especially the management of Patient Shelter House. The data are obtained based on the interviewing of six informants consisting of three IZI administrators who managed RSP IZI directly and three other beneficiaries of RSP IZI. The requirement to be a beneficiary of RSP IZI must be Muslim, destitute or poor and domiciled outside Surabaya. The results of the study, the implementation of ZIS LAZNAS Zakat Indonesia Initiative fund management is in accordance with Law No. 23 of 2011 concerning the management of zakat.Keywords: Zakah, Infak, Shadaqah, Patient Shelter House (RSP).REFFERENCESAl-Quran dan Terjemahannya. (2011). Jakarta : Departemen Agama Republik Indonesia.Ali, Muhammad Daud. 1998. Sistem Ekonomi Islam Zakat dan Wakaf. Jakarta: Universitas Indonesia Press.Azhar, Hary Aziz et.al. 2017. Indonesia Zakat Development Report Zakat dan Pemberdayaan. Surabaya: Airlangga University Press.Bungin, Burhan. 2008. Analisis Data Penelitian Kualitatif Pemahaman Filosofis dan Metodologis ke Arah Penguasaan Model Aplikasi. Jakarta : Raja Grafindo Persada.Hafidhuddin, Didin. 2002. Zakat Dalam Perekonomian Modern. Jakarta: Gema Isani Press.Kartika, Elsi Sari. 2006. Pengantar Hukum dan Wakaf. Jakarta: PT Grasindo.Mamik. 2014. Manajemen Mutu Pelayanan Kesehatan dan Kebidanan. Sidoarjo: Zifatama Publisher.Qardawi, Yusuf. 2011. Hukum Zakat. Bogor: Pustaka Litera Antar Nusa.Ryandono, Muhammad Nafik Hadi. 2008. Ekonomi ZISWAQ (Zakat, Infak, Shadaqah dan Waqaf). Surabaya: IFDI dan Cenforis.Samiun, Ali.2017. Pengertian Infak dan Dasar Hukum Infak. (Online) (diakses 20 April 2019 http://www.informasiahli.com/2017/01/pengertian-infak-dan-dasar-hukum-infak.html).Sarwat, Ahmad. 2011. Seri Fiqih Kehidupan 4 Zakat. Jakarta: DU Publishing.Undang-undang Republik Indonesia Nomor 23 tahun 2011 Tentang Pengelolaan Zakat.Uyun,Q. 2015. Zakat, Infak, Shadaqah, dan Wakaf Sebagai Konfigurasi Filantropi Islam. Islamuna, Vol.2(2).Yin, K. Robert. 2015. Studi Kasus: Desain dan Metode. Jakarta: Rajawali Pers.https://izi.or.id. Diakses pada hari Jumat 15 maret 2019, jam 10.00 WIBhttp://www.bps.co.id. Diakses pada hari Jumat 15 maret 2019, jam 10.00 WIB